(untitled) (Indian Journal of Chemistry (IJC), 2025)
Metal complexes of antibiotic have demonstrated significant effectiveness in inhibiting the growth or eradicating microorganisms. The harmful microbes are gradually developing resistance to modern antibiotics through a variety of cellular defense mechanisms. Consequently, pursuit of alternative drug molecules is essential in the fight against the resistant microorganisms. Researchers have been investigating for new drugs and methods to enhance the effectiveness of existing antibiotics through concentrating on antibiotic complexes that incorporate metal ions. The coordination of these metal ions has the potential to elevate the bioactivity of antibiotics. Reactions involving gentamicin sulfate and different metal salts have been employed to form gentamicin sulfate complexes with various metals. Several methods, such as Fourier-transform infrared (FTIR) spectroscopy, melting point measurements, and solubility evaluations were used to characterize the synthesized complex compounds. The antimicrobial efficacy of the complexes was evaluated against nine pathogenic bacteria and four fungal strains. Some of the complexes showed enhanced antibacterial and antifungal effects than the corresponding antimicrobial agent. Complexes formed by Gentamicin with strontium and with cobalt shows enhanced antibacterial activity against Staphylococcus aureus and Salmonella abony, respectively. Furthermore, the antifungal efficacy of Ni, Zn, Fe, and Mg complexes of gentamicin against Aspergillus fumigatus, as well as the Zn, Fe, and Mg complexes of gentamicin against Aspergillus niger, was increased.